h y Michael Hilgers. - Hilgers, Michael; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer Vieweg, 2022)
The aim of this work, consisting of 9 individual, self-contained booklets, is to describe commercial vehicle technology in a way that is clear, concise and illustrative. Compact and easy to understand, it provides an overview of the technology that goes into modern commercial vehicles. Starting from the customer's fundamental requirements, the characteristics and systems that define the design of the vehicles are presented knowledgeably in a series of articles, each of which can be read and studied on their own. In this volume, The Driver's Cab, the vehicle cab is reviewed in simple terms for the layman. The three functions it must support, driving, living and sleeping and the features of the cab equipment provided therefor are presented. Important systems of the driver's cab are discussed in readily understandable terms. Content The cab concept.- Functions of the cab.- Cab technology.- Abbreviations and symbols. The target groups Participants in master classes and those studying individual aspects of commercial vehicle technology Professors and lecturers instructing in the field of commercial vehicle technology Consultants and experts who need background knowledge and technical expertise regarding commercial vehicle technology Personnel working in the commercial vehicle technology or supply industry who are assigned to a new work area Cost planners and logistics companies The Author Dr. Michael Hilgers .
The cab concept -- Functions of the cab -- Cab technology -- Abbreviations and symbols.
Keywords: Automotive engineering; Engines; Automotive Engineering; Engine Technology; Trucks -- Design and construction; Automobiles -- Interiors